On Nations and International Boundaries – The European Case - Biger, Gideon (European Spatial Research and Policy, 2011)
It seems that our world is made of mainly nation states – independent states based on one particular nation, sometimes with some minorities in that state. Thus the model seams to be ‘a nation is establishing its boundaries’. On the other hand, our world also has the ‘boundaries that made a nation’ model, in which a nation was created after boundaries were drawn. Most independent European countries belong to the first model but Spain, Belgium, and five tiny states belong to the second model.